REVOLUSI DESA BANYUWANGI DENGAN TEH CINDY; MENGOPTIMALKAN POTENSI LOKAL MELALUI PLATFORM DIGITAL - Rahmawati, Ima; Hasanah, Siti Lutfiatul; Maulana, Agung; Maulana, Muhammad Restu; Mulyati, Embun; Lestari, Hana (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
After conducting a survey, we found several obstacles in Banyuwangi Village, especially in the MSME sector which has difficulties related to marketing, access to information, and business legality. INAIS Sahid Bogor KKN students also identified a lack of coordination between the community and the village. Teh Cindi application is a digital solution to facilitate product marketing, provide the "Hello Village" feature, access village news, and apply for halal certification online. This research uses descriptive qualitative methods with data collection techniques through observation and interviews. Sources of information came from documents and informants, consisting of MSME owners, the village government, and the people of Banyuwangi Village. Teh Cindi Innovation Program provides many benefits, especially in facilitating the distribution of MSME products and increasing access to information and community coordination with the village through existing features.